Transcranial Alternating Current Stimulation of the Primary Motor Cortex after Skill Acquisition Improves Motor Memory Retention in Humans: A Double-Blinded Sham-Controlled Study. Issue 1 (6th August 2020) - Yamaguchi, Tomofumi; Svane, Christian; Forman, Christian Riis; Beck, Mikkel Malling; Geertsen, Svend Sparre; Lundbye-Jensen, Jesper; Nielsen, Jens Bo
Abstract: Consolidation leading to retention of motor memory following motor practice involves activity-dependent plastic processes in the corticospinal system. To investigate whether beta-band transcranial alternating current stimulation (tACS) applied immediately following skill acquisition can enhance ongoing consolidation processes and thereby motor skill retention 20 adults participated in a randomized, double-blinded, sham-controlled study. Participants received tACS at peak beta-band corticomuscular coherence (CMC) frequency or sham tACS for 10 min following practice of a visuomotor ankle dorsiflexion task. Performance was measured as the average percentage time on target. Electroencephalograhy (EMG) was measured at Cz and EMG from the right tibialis anterior muscle. CMC and intramuscular coherence (IMC) were estimated during 2-min tonic dorsiflexion. Motor skill retention was tested 1 and 7 days after motor practice. From the end of motor practice to the retention tests, motor performance improved more in the tACS group compared with the sham tACS group after 1 ( P = 0.05) and 7 days ( P < 0.001). At both retention tests, beta-band IMC increased in the tACS group compared with post-tACS. Beta-band CMC increased in the tACS group at retention day 1 compared with post-tACS. Changes in CMC but not IMC were correlated with performance 1 and 7 days following practice. This study shows that tACS applied at beta-band CMC frequency improves consolidation following visuomotor practice and increases beta-band CMC and IMC. We propose that oscillatory beta activity in the corticospinal system may facilitate consolidation of the motor skill.